2012
DOI: 10.1039/c2cc18189d
|View full text |Cite
|
Sign up to set email alerts
|

Diindenothieno[2,3-b]thiophene arene for efficient organic photovoltaics with an extra high open-circuit voltage of 1.14 ev

Abstract: We report a novel diindenothieno[2,3-b]thiophene ladder-type hexacyclic arene for constructing a donor-acceptor copolymer PDITTDTBT. A device based on PDITTDTBT:PC(71)BM exhibited a high V(oc) of 0.92 V with an impressive PCE of 5.8%, while a PDITTDTBT:DMPCBA-based device showed an extra high V(oc) of 1.14 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…In particular, power conversion efficiency (PCE) of 8–9% in a single junction device has been demonstrated 1–5. Among various materials developed for BHJ devices, the multifused‐ring conjugated polymers are particularly interesting due to their superior optical and electrical properties 6–20. The highly fused aromatic/heteroaromatic units enhance effective conjugation of the polymer backbone to facilitate electron delocalization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, power conversion efficiency (PCE) of 8–9% in a single junction device has been demonstrated 1–5. Among various materials developed for BHJ devices, the multifused‐ring conjugated polymers are particularly interesting due to their superior optical and electrical properties 6–20. The highly fused aromatic/heteroaromatic units enhance effective conjugation of the polymer backbone to facilitate electron delocalization.…”
Section: Methodsmentioning
confidence: 99%
“…This has inspired vigorous efforts to modify the IDT backbone, such as changing the bridging atoms or side‐chains to improve polymer packing for better charge transport or light absorption 9, 12, 25–27. Larger fused‐rings by extending the IDT backbone,10, 11, 16, 18, 19, 28–30 increasing the number of aromatic rings, or changing the sequence of tethered aromatic units on the backbone all have been tried and generated a wide variety of multiple fused‐ring systems 17, 20. For example, Cheng et al have reported a novel seven‐ring system by fusing a fluorene unit and two thiophene units together.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several highly coplanar donor units with extended π‐conjugation by fastening or fusing adjacent rings have been reported. The central cores can be benzene, thiophene, and other fused three rings like fluorene, carbazole, silole, and benzodithiophene 19–26. The outer thiophene or benzene rings are covalently fastened or fused to the central cores, affording largely coplanar and symmetric structures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the C 2h symmetry and coplanar geometry allow more ordered packing and stronger interchain interactions to achieve exceptional hole mobility, which is beneficial for J sc . Cheng et al [118] have reported a multifused hexacyclic diindenothieno [2,3-d]thiophene (DITT) unit, where the central TT ring is connected with two outer phenyl rings through two embedded cyclopentadienyl (CP) rings. This monomer was polymerized by Suzuki coupling with 4,7-bis(5-bromo-2-thienyl)-2,1,3-benzothiadiazole (DTBT) acceptor to afford a new class of alternating D-A conjugated polymers P80.…”
Section: Conjugated Polymers Containing Multifused Alternatementioning
confidence: 99%